Efektivitas Pengelolaan Administrasi Pemerintahan Desa dalam Penyaluran Bantuan di Kabupaten Cirebon: Analisis Hukum Tata Negara - Della Kristi Noviyanti; Izzuddin Izzuddin; Anez Yanuar Pradini (Hukum, 2026)
Village government administration plays an important role in ensuring that Village Direct Cash Transfers are distributed accurately, promptly, transparently, and accountably. This study examines the effectiveness of village government administration in distributing Village Direct Cash Transfers in Cirebon Regency and assesses its compliance with village financial management principles and general principles of good governance. The study employed an empirical legal method using a socio-legal approach and a qualitative case study design. Data were collected through observation, semi-structured interviews, and document analysis covering beneficiary data collection, verification, village deliberations, recipient determination, distribution, reporting, and supervision. The data were analyzed using indicators of targeting accuracy, timeliness, data accuracy, transparency, accountability, participation, responsiveness, and legal compliance. The findings indicate that village governments have implemented the administrative stages of cash transfer distribution, although their effectiveness remains affected by delays in data updating, potential targeting errors, limited administrative capacity, insufficient public information, and underdeveloped complaint mechanisms. The distribution process should be strengthened through layered data verification, improved staff competency, a stronger supervisory role for village consultative bodies, orderly documentation, and consistent oversight. These measures are necessary to ensure that the program complies with the principles of legal certainty, accuracy, transparency, public interest, and good public service.